Fluororubber composition applied to lithium battery sealing and preparation method thereof

By optimizing the formulation and preparation process of the fluororubber composition, a fluororubber sealing ring with excellent shape recovery ability and electrolyte resistance was prepared, which solved the shortcomings of lithium battery sealing rings in terms of electrolyte corrosion resistance and compression set, and improved the safety and service life of lithium batteries.

CN121293657APending Publication Date: 2026-01-09HAINING JIACHENG RUBBER CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511591502.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing lithium battery fluororubber seals are insufficient in terms of resistance to electrolyte corrosion and compression set, failing to meet the requirements of the new standard and affecting the safety performance and service life of lithium batteries.

Method used

Fluororubber sealing rings are prepared by compression molding using a composition of fluororubber raw rubber, crosslinking agent, peroxide, reinforcing composition, acid absorbent, corrosion resistant additive, dispersant, and release agent in a specific ratio. The combination of crosslinking agent and peroxide is optimized, silica and carbon black are added as reinforcing agents, a nano-layered corrosion resistant additive is added, the acid absorbent composition is optimized, vinyl silicone oil and fluorosilane are used as dispersants, and the composition of the release agent is adjusted to ensure the sealing ring's resistance to electrolyte corrosion and its shape recovery ability.

Benefits of technology

The fluororubber sealing ring has improved its resistance to electrolyte corrosion, wear resistance, weather resistance and tensile strength, and reduced the compression set, thus meeting the high safety and long life requirements of lithium battery sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to the technical field of fluororubber sealing ring preparation, in particular to a fluororubber composition applied to lithium battery sealing and a preparation method of the fluororubber composition. The invention discloses a fluororubber composition applied to lithium battery sealing. The fluororubber composition is prepared from the following raw materials in parts by weight: 100 parts of raw fluororubber, 3.8-4.2 parts of a cross-linking agent, 1.3-1.6 parts of peroxide, 28-36 parts of a reinforcing composition, 6-12 parts of an acid acceptor, 3-5 parts of a corrosion-resistant additive, 0.5-2 parts of a dispersing agent and 0.5-1 part of a release agent. The fluororubber sealing ring prepared from the fluororubber composition disclosed by the invention has good electrolyte corrosion resistance stability and also has good wear resistance, weather resistance and tensile mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluororubber sealing ring preparation technology, and in particular to a fluororubber composition for use in lithium battery sealing. Background Technology

[0002] Fluororubber possesses excellent properties such as airtightness, heat resistance, oxidation resistance, oil resistance, solvent resistance, corrosion resistance, and weather resistance. As a sealing ring material, it can be used in extreme environments, such as the automotive industry, chemical processes, and aerospace. In the lithium battery field, fluororubber sealing rings are mainly used for electrolyte encapsulation, which requires fluororubber to have excellent resistance to electrolyte corrosion.

[0003] The national standard GB / T 37996-2019 "Rubber Seals for Power Lithium Batteries" specifies the performance requirements for fluororubber compounds. Taking a fluororubber sealing ring with a hardness of 70±5A as an example, the tensile strength is ≥13MPa, the elongation at break is ≥200%, the compression set (200℃×48h) is ≤30%, the electrolyte resistance (70℃×168h) is such that the color of the electrolyte does not change or changes slightly after immersion and the mass change rate is ≤30%, and the dimensional expansion rate after immersion in the electrolyte is ≤20%.

[0004] With the introduction of the new lithium battery standard – IEC 60086-4:2025 – higher requirements have been placed on the safety performance of lithium batteries. This necessitates that fluororubber sealing rings possess lower compression set and more durable electrolyte resistance. To address this, the inventors have provided a fluororubber composition with excellent shape recovery and electrolyte resistance for use in lithium battery sealing. Summary of the Invention

[0005] To improve the sealing quality and safety stability of lithium battery electrolytes and promote the high-quality and safe development of lithium batteries, this invention provides a fluororubber composition for lithium battery sealing and its preparation method. The composition exhibits low compression set, excellent shape recovery ability, and electrolyte resistance, thereby improving the safe performance of lithium batteries.

[0006] The fluororubber composition for sealing lithium batteries provided by this invention is achieved through the following technical solution:

[0007] A fluororubber composition for sealing lithium batteries comprises the following raw materials in parts by weight: 100 parts of fluororubber raw rubber, 3.8-4.2 parts of crosslinking agent, 1.3-1.6 parts of peroxide crosslinking agent, 28-36 parts of reinforcing composition, 6-12 parts of acid absorber, 3-5 parts of corrosion resistant additive, 0.5-2 parts of dispersant, and 0.5-1 part of release agent.

[0008] The fluororubber sealing ring prepared by the fluororubber composition of the present invention has good resistance to electrolyte corrosion, as well as good wear resistance, weather resistance and tensile strength.

[0009] Preferably, the fluororubber raw rubber is any one of Chemours GF200S, Chemours GF600S, Daikin G932, Solvay P459, Solvay P959, Solvay PL 458, Solvay PL 958, and 3M-FP03820.

[0010] Preferably, the crosslinking agent includes at least one of triallyl isocyanurate, trimethylallyl isocyanate, tri(2-acryloyloxyethyl) isocyanurate, diallyl isocyanurate amidation derivative, and mono(acryloyloxyethyl) isocyanurate amidation derivative.

[0011] Preferably, the peroxide is at least one of dicumyl peroxide, benzoyl peroxide, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane.

[0012] By using a combination of crosslinking agents and peroxides, the fluororubber sealing ring is guaranteed to have a low compression set rate, while also being given good resistance to corrosive media. When applied to lithium battery sealing, it exhibits excellent resistance to acidic lithium battery electrolytes.

[0013] Preferably, the reinforcing composition consists of a reinforcing agent and a filler, wherein the reinforcing agent is any one of silica combined with carbon black, calcium oxide, and zinc oxide; and the filler is any one of barium sulfate, titanium dioxide, and calcium fluoride.

[0014] Zinc oxide in the reinforcing agent strengthens the fluororubber composition, improving tear resistance, abrasion resistance, and hardness, enhancing dynamic mechanical properties, reducing hysteresis loss, and increasing resilience. Furthermore, it significantly inhibits degradation by ozone, ultraviolet radiation, and thermal oxidation, improving the weather resistance of the fluororubber composition. In addition, it effectively prevents overheating degradation of rubber products at high temperatures: its high thermal conductivity helps disperse heat generated during processing, avoiding localized overheating; and it reacts with rubber degradation products, slowing down the thermal degradation process.

[0015] Due to the potential environmental risks associated with zinc oxide, it can be replaced by rubber vulcanizing activator Type II, or by combining rubber vulcanizing activator Type II with zinc oxide.

[0016] The reinforcing agent is composed of carbon black and silica, and the amount of carbon black added is ≤4 phr.

[0017] Fluororubber seals manufactured using a fluororubber composition via compression molding have specific insulation performance requirements: at 500VDC, the insulation resistance of the fluororubber seal must be >5000 Mohm, and after 50% compression, the insulation resistance must be >3000 Mohm. Therefore, silica, with its excellent insulation properties, is used as the primary reinforcing agent, with carbon black as an auxiliary reinforcing agent. The carbon black addition amount should be ≤4 phr. Adding more than 5 phr will negatively impact the insulation performance of the fluororubber seal, causing it to fail to meet CATL's quality requirements.

[0018] Preferably, the corrosion-resistant additive is any one of fluorinated graphite powder, fluorinated graphene, MXene nanosheets, nano-hexagonal boron nitride, and sheet-like nano-molybdenum disulfide.

[0019] Fluorinated graphite powder and fluorinated graphene improve their electrical conductivity through fluorine, and they have good insulation properties. Fluororubber sealing rings made from them have guaranteed insulation performance.

[0020] By adding corrosion-resistant additives with nano-layered structures, the electrolyte erosion resistance, tear strength, tensile strength, weather resistance and compression set of fluororubber compositions can be improved.

[0021] More preferably, the corrosion-resistant additive is at least one of nano-hexagonal boron nitride, sheet-like nano-molybdenum disulfide combined with fluorinated graphene, fluorinated graphene powder, and MXene nanosheets.

[0022] The advantages of fluorinated graphene as a corrosion-resistant additive are: it ensures the insulation performance of fluororubber sealing rings while retaining the advantages of graphene: improved mechanical properties and resistance to electrolyte corrosion. It can also give fluororubber sealing rings good antibacterial and hygienic properties and electromagnetic shielding properties, thus better meeting the sealing requirements of lithium batteries.

[0023] The remaining MXene nanosheets, nano-hexagonal boron nitride, and flake-shaped nano-molybdenum disulfide in the corrosion-resistant additives have generally low electrical conductivity and are added at levels ≤5 phr. They have little impact on the insulation performance of fluororubber sealing rings. While ensuring the insulation performance of fluororubber sealing rings, they can improve the barrier properties, electrolyte corrosion resistance, mechanical properties, wear resistance, and tear resistance of fluororubber sealing rings.

[0024] Preferably, the dispersant is composed of vinyl silicone oil and fluorosilane; the vinyl silicone oil is vinyltrimethoxysilane and / or vinyltri(2-methoxyethoxy)silane; the fluorosilane is any one of tridecafluorooctyltrimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, and 3,3,3-trifluoropropylmethyldimethoxysilane.

[0025] More preferably, the dispersant is composed of vinyl silicone oil and fluorosilane.

[0026] Fluorosilanes can be used to surface-modify fillers, improving their dispersion within the fluororubber matrix and thus ensuring the physicochemical properties of the prepared fluororubber sealing rings. Vinyl silicone oil can also be used to surface-modify fillers, improving their compatibility with fluororubber raw materials to some extent, but its modification effect is less pronounced than that of fluorosilanes. However, double bonds on the surface of vinyl silicone oil-modified fillers chemically graft with double bonds in the fluororubber matrix under thermal and peroxide conditions. This facilitates filler anchoring within the fluororubber matrix, preventing filler precipitation due to compatibility issues, which would affect filler distribution uniformity and reduce the weather resistance and service life of the fluororubber seals. Furthermore, fillers chemically grafted into the fluororubber matrix can improve the overall crosslinking density, thereby enhancing the barrier properties, electrolyte corrosion resistance, and compression set of the fluororubber sealing rings. However, a high vinyl content on the filler surface can lead to excessive crosslinking density, which can negatively impact the hardness, elasticity, and service life of the fluororubber sealing rings. Therefore, when vinyl silicone oil and fluorosilane form a compound dispersant, vinyl silicone oil accounts for 20-40 wt% of the dispersant.

[0027] The reinforcing composition, acid absorber, and corrosion resistant additives treated with dispersant can be evenly distributed inside the fluororubber matrix, ensuring the mechanical properties and resistance to electrolyte corrosion of the fluororubber.

[0028] In addition, the double bonds contained on the surface of the reinforcing composition, acid absorber, and corrosion resistant additives undergo double bond polymerization with the double bonds contained in fluororubber under the action of crosslinking agents and peroxides. This can prevent the precipitation on the surface of the reinforcing composition, acid absorber, and corrosion resistant additives, thereby improving the mechanical strength durability, electrolyte erosion resistance durability, and service life of fluororubber.

[0029] Preferably, the acid absorbent is composed of magnesium oxide, calcium hydroxide, and lead oxide in a mass ratio of (2-3):(2-5):(3-5).

[0030] The addition of magnesium oxide to acid absorbers can improve the heat resistance of fluororubber compositions.

[0031] The addition of calcium hydroxide can improve the compression set of fluororubber compositions.

[0032] The addition of lead oxide can improve the acid resistance of fluororubber compositions, giving them good resistance to acid corrosion in acidic lithium battery electrolytes.

[0033] Fluororubber seals have high requirements for resistance to electrolyte corrosion and compression set, so the content of calcium hydroxide and lead oxide in the acid absorbent is relatively high.

[0034] An acid scavenger composed of magnesium oxide, calcium hydroxide, and lead oxide can improve the heat resistance, weather resistance, compression set, acid erosion resistance, tear resistance, abrasion resistance, reduce hysteresis loss, improve resilience, and improve hot processing performance of fluororubber compositions.

[0035] Because lead oxide poses potential environmental hazards, the inventors overcame the problem of decreased deformation recovery performance caused by zero lead oxide addition by adjusting the formulation of corrosion-resistant additives, thus improving the environmental performance of fluororubber seals.

[0036] Preferably, the release agent is any one of 3853 fine pure fluorine wax, PTFE / PE micro powder wax ST-563F, polytetrafluoroethylene modified wax 9610F, and zinc stearate.

[0037] The present invention provides a method for preparing a fluororubber composition for sealing lithium batteries, which is achieved through the following technical solution:

[0038] A method for preparing a fluororubber composition for sealing lithium batteries, comprising the following steps:

[0039] Step 1: The reinforcing composition, acid absorber, and corrosion resistant additive are surface-treated with a dispersant to obtain a mixed filler;

[0040] Step 2: Mix the mixed filler from Step 1 with the crosslinking agent, peroxide, and release agent until homogeneous to obtain the premix.

[0041] Step 3: Add the fluororubber raw rubber to a two-roll mill and mix at 40-60℃ for 1-2 minutes. Then add the premix from Step 2, make triangular bags 2-6 times, and pass through a thin tube 4-8 times. Let it stand for 1-24 hours to obtain the compound rubber.

[0042] Step 4: Compression molding to prepare fluororubber sealing rings: The compounded rubber is injected into the molding die, followed by two-stage vulcanization treatment by moving the die. The first stage vulcanization temperature is 170-185℃, the pressure is 8-16MPa, and the time is 8-12 minutes; the second stage vulcanization temperature is 210-230℃ and the time is 2-6 hours. Finally, hot pressing is performed at 200-220℃ and 1-3 MPa pressure for 40-80 minutes. After natural cooling to room temperature, the rings are demolded and the burrs are trimmed to obtain fluororubber sealing rings for lithium battery sealing.

[0043] The preparation method of the present invention is relatively simple and mature, and is easy to achieve large-scale production.

[0044] In summary, the present invention has the following advantages:

[0045] 1. The fluororubber sealing ring prepared by the fluororubber composition of the present invention has good resistance to electrolyte corrosion, as well as good wear resistance, weather resistance and tensile mechanical strength.

[0046] 2. In this invention, the vulcanization components have been optimized and cross-linking agents and peroxide cross-linking agents are used in combination. While ensuring that the fluororubber sealing ring has a low compression set, the resistance of the fluororubber sealing ring to corrosive media is improved. When applied to lithium battery sealing, it can have excellent resistance to corrosion by acidic lithium battery electrolyte.

[0047] 3. In this invention, the acid absorbent components are optimized to improve the heat resistance, weather resistance, compression set, acid erosion resistance, tear resistance, abrasion resistance, reduce hysteresis loss, improve resilience, and hot processing performance of the fluororubber composition.

[0048] 4. The corrosion-resistant additives added in this invention, when used in combination with an appropriate amount of plasticizer, improve the electrolyte erosion resistance of the fluororubber composition, and also improve the compression set, tensile strength, tear strength, abrasion resistance, and weather resistance of the fluororubber composition.

[0049] 5. The preparation method of the present invention is relatively simple and mature, and is easy to achieve large-scale production. Detailed Implementation

[0050] The technical solution of the present invention will be further described below with reference to comparative examples and embodiments.

[0051] Example: A fluororubber composition for sealing lithium batteries, comprising the following parts by weight of raw materials: 100 parts of fluororubber raw rubber, 3.8-4.2 parts of crosslinking agent, 1.3-1.6 parts of peroxide, 28-36 parts of reinforcing composition, 6-12 parts of acid absorber, 3-5 parts of corrosion resistant additive, 0.5-2 parts of dispersant, and 0.5-1 part of release agent.

[0052] The fluororubber raw material is any one of Chemours GF200S, Chemours GF600S, Daikin G932, Solvay P459, Solvay P959, Solvay PL 458, Solvay PL 958, and 3M-FP03820. Preferably, the fluororubber raw material is Chemours GF600S.

[0053] The peroxide is at least one of dicumyl peroxide (DCP), benzoyl peroxide (BPO), and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane.

[0054] Preferably, the peroxide is Luperox® 101XL45.

[0055] The crosslinking agent includes at least one of triallyl isocyanurate, trimethylallyl isocyanate, tri(2-acryloyloxyethyl) isocyanurate, diallyl isocyanurate amidation derivative, and isocyanurate mono(acryloyloxyethyl) isocyanurate amidation derivative.

[0056] The amidated derivative of diallyl isocyanurate is prepared by amidation reaction of diallyl isocyanurate (CAS: 6294-79-7, DAI) and 2-(trifluoromethyl)acrylic acid (CAS: 381-98-6, TFA) in a molar ratio of 1:1.

[0057] The isocyanurate mono(acryloyloxyethyl) ester amidation derivative is prepared by isocyanurate mono(acryloyloxyethyl) ester (CAS: 88403-03-6) and 2-(trifluoromethyl)acrylic acid (CAS: 381-98-6) in a molar ratio of 1:2.

[0058] The reinforcing composition consists of a reinforcing agent and a filler. The reinforcing agent is composed of carbon black and silica, and may also contain an appropriate amount of calcium oxide to improve the compression set of the fluororubber seal. The amount of carbon black added to the reinforcing agent should be ≤4 phr. Adding more than 5 phr will affect the insulation performance of the fluororubber seal, causing it to fail to meet CATL's quality requirements.

[0059] More preferably, the reinforcing agent is composed of 25 wt% Cabot MT N990 carbon black and 75 wt% PST-Q02 silica, which can ensure the insulation performance of the fluororubber seal (insulation resistance of the fluororubber seal >5000 Mohm at 500V DC voltage, and insulation resistance of the fluororubber seal >3000 Mohm after 50% compression).

[0060] To reduce the amount of reinforcing agent used, a suitable amount of filler can be added, that is, an equal amount of silica can be replaced with an equal amount of filler. The reinforcing composition can consist of a reinforcing agent and a filler, which can reduce the production cost of fluororubber rings to a certain extent. The filler can be any one of barium sulfate, titanium dioxide, or calcium fluoride. Ultrafine barium sulfate is generally chosen as the filler.

[0061] To improve the resistance of fluororubber to electrolyte corrosion, 3-5 phr of corrosion-resistant additives are added to the fluororubber composition formulation. These additives are any one of the following: nano-layered fluorinated graphite powder, fluorinated graphene, MXene nanosheets, nano-hexagonal boron nitride, and sheet-like nano-molybdenum disulfide.

[0062] The dispersant is composed of vinyl silicone oil and fluorosilane. Preferably, the dispersant is composed of vinyl silicone oil and fluorosilane, and the mass ratio of vinyl silicone oil to fluorosilane is 1:(0.5-2).

[0063] The vinyl silicone oil is vinyltrimethoxysilane KH-171 (CAS: 2768-02-7) and / or vinyltris(2-methoxyethoxy)silane KH-171 (CAS: 1067-53-4).

[0064] The fluorosilane is any one of the following: tridecafluorooctyltrimethoxysilane KH-1331 (CAS: 85857-16-5), 3,3,3-trifluoropropyltrimethoxysilane KH-331 (CAS: 429-60-7), and 3,3,3-trifluoropropylmethyldimethoxysilane KH-3121 (CAS: 358-67-8).

[0065] Fluororubber sealing rings require high resistance to electrolyte corrosion and low compression set. Therefore, the acid absorbent contains relatively high levels of calcium hydroxide and lead oxide, specifically magnesium oxide, calcium hydroxide, and lead oxide in a mass ratio of (2-3):(2-5):(3-5). Preferably, the acid absorbent is composed of magnesium oxide, calcium hydroxide, and lead oxide in a mass ratio of 2:4:4.

[0066] Due to the potential environmental risks associated with active nano-zinc oxide, it can be replaced by the 2000-mesh rubber vulcanizing activator - Jieculian II from Guangxi Liankehua New Materials Co., Ltd., or by using Jieculian II in combination with zinc oxide. Specifically, the reinforcing agent can be any one of the following: silica combined with carbon black, silica, calcium oxide, or Jieculian II rubber vulcanizing activator.

[0067] The release agent is any one of the following: 3853 fine pure fluorine wax, PTFE / PE micro powder wax ST-563F, polytetrafluoroethylene modified wax 9610F, and zinc stearate.

[0068] A method for preparing a fluororubber composition for sealing lithium batteries includes the following steps:

[0069] Step 1: The reinforcing composition, acid absorber, and corrosion resistant additive are surface-treated with a dispersant to obtain a mixed filler;

[0070] Step 2: Mix the mixed filler from Step 1 with the crosslinking agent, peroxide, and release agent until homogeneous to obtain the premix.

[0071] Step 3: Add the fluororubber raw rubber to a two-roll mill and mix at 40-60℃ for 1-2 minutes. Then add the premix from Step 2, make triangular bags 2-6 times, and pass through a thin tube 4-8 times. Let it stand for 1-24 hours to obtain the compound rubber.

[0072] Step 4: Compression molding to prepare fluororubber sealing rings: The compounded rubber is injected into the molding die, followed by two-stage vulcanization treatment by moving the die. The first stage vulcanization temperature is 170-185℃, the pressure is 8-16MPa, and the time is 8-12 minutes; the second stage vulcanization temperature is 210-230℃ and the time is 2-6 hours. Finally, hot pressing is performed at 200-220℃ and 1-3 MPa pressure for 40-80 minutes. After natural cooling to room temperature, the rings are demolded and the burrs are trimmed to obtain fluororubber sealing rings for lithium battery sealing.

[0073] Example 1: A fluororubber composition for sealing lithium batteries, comprising the following raw materials in parts by weight: 100 parts of fluororubber raw rubber (Cholmos GF600S), 4 parts of crosslinking agent - triallyl isocyanurate (TAIC-75%, CAS: 1025-15-6), 1.5 parts of Luperox® 101XL45 (CAS: 78-63-7), 4 parts of Cabot N990 carbon black (brand: Kenkaber, supplier: Shanghai Kaiyin Chemical Co., Ltd.), 21 parts of white carbon black PST-Q02 (hydrophilic nano silica PST-Q02, primary particle size 20nm, Nanjing Baoket New Materials Co., Ltd.), 2 parts of magnesium oxide (Hangzhou Jikang New Materials Co., Ltd., nano magnesium oxide SS-MG30, primary particle size: 30-50nm), and 4 parts of calcium hydroxide HP-XL (1000 mesh, Shenzhen Longlifeng Materials Co., Ltd.). The following materials were used: 4 parts lead oxide (CAS: 1317-36-8, Aladdin), 5 parts zinc oxide (nano-active zinc oxide SS-Z20, primary particle size SEM: 20nm, Hangzhou Jikang New Materials Co., Ltd.), 0.3 parts fluorinated graphene [Cenfu (Shanghai) Fine Chemicals Co., Ltd., CAS: 51311-17-2], and 3.7 parts sheet-like nano molybdenum disulfide (Shanghai Chaowei Nanotechnology Co., Ltd., item number CW-MoS2-002, average particle size: 600nm, specific surface area: 12.4m²). 2 / g), 0.3 parts of vinyltrimethoxysilane KH-171, 0.7 parts of 3,3,3-trifluoropropylmethyldimethoxysilane KH-3121, and 0.5 parts of 3853 fine pure fluorine wax (Jining Fangyu Chemical Co., Ltd., white micro powder, melting point: 320℃, particle size: 6.5µm).

[0074] A method for preparing a fluororubber composition for sealing lithium batteries includes the following steps:

[0075] Step 1: Add 0.3 parts of vinyltrimethoxysilane, 0.7 parts of 3,3,3-trifluoropropylmethyldimethoxysilane, 4 parts of Cabot N990 carbon black, 21 parts of PST-Q02 silica, 2 parts of magnesium oxide, 4 parts of calcium hydroxide, 4 parts of lead oxide, 5 parts of zinc oxide, 1 part of fluorinated graphene, and 3 parts of flake-shaped nano molybdenum disulfide to a kneader and knead and disperse at 50°C for 1 hour to obtain a mixed filler.

[0076] Step 2: Add 0.5 parts of 3853 fine pure fluorinated wax to a kneader containing mixed fillers, knead and disperse at 50°C for 15 minutes, then adjust the kneading temperature to 40°C, add 4 parts of crosslinking agent - triallyl isocyanurate and 1.5 parts of Luperox® 101XL45, knead and disperse at 40°C for 15 minutes, mix evenly, and obtain a premix.

[0077] Step 3: Add the fluororubber raw rubber - Chemours GF600S to a two-roll mill and mix at 60°C for 2 minutes. Then add the premix from Step 2, make three triangular bags, and feed the material through a thin tube six times. Let it stand for 24 hours to obtain the compound rubber.

[0078] Step 4: Compression molding to prepare fluororubber sealing rings: The compounded rubber is injected into the molding die, followed by two-stage vulcanization treatment by moving the die. The first stage vulcanization temperature is 177℃, the pressure is 10.0MPa, and the time is 8 minutes; the second stage vulcanization temperature is 230℃, and the vulcanization is carried out at normal pressure for 4 hours. Finally, the rings are hot-pressed at 210℃ and 2 MPa pressure for 60 minutes, allowed to cool naturally to room temperature, demolded, and the burrs are trimmed to obtain fluororubber sealing rings for lithium battery sealing.

[0079] In Example 1, the insulation resistance of the fluororubber sealing ring was measured using a resistance tester under conditions of 500V DC / 2s. The insulation resistance of the fluororubber sealing ring was 5.87*10. 9 Ω, greater than 5000 Mohm (5*10 9 (Ω), insulation resistance after 50% compression is 3.45*10 9 Ω, greater than 3000 Mohm (3*10 9 (Ω), which meets CATL's insulation requirements for fluororubber seals.

[0080] It is generally known that CATL's insulation properties for fluororubber seals are as follows: Under normal conditions, the insulation resistance of fluororubber seals is >5000 Mohm, and after 50% compression, the insulation resistance is >3000 Mohm.

[0081] The difference between Control Group 1 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of Cabot N990 carbon black and 21 parts of silica PST-Q02 were replaced with 8 parts of Cabot N990 carbon black and 17 parts of silica PST-Q02.

[0082] The insulation resistance of the fluororubber sealing ring prepared in control group 1 was measured using a resistance meter under conditions of 500V DC / 2s. The insulation resistance of the fluororubber sealing ring was 2.14*10. 8 Ω, below 5000 Mohm (5*10 9 (Ω), insulation resistance after 50% compression is 1.26*10 8 Ω, below 3000 Mohm (3*10 9 (Ω), which cannot meet CATL's insulation requirements for fluororubber seals.

[0083] The difference between Control Group 2 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of Cabot N990 carbon black and 21 parts of silica PST-Q02 were replaced with 5 parts of Cabot N990 carbon black and 20 parts of silica PST-Q02.

[0084] The insulation resistance of the fluororubber sealing ring prepared in control group 2 was measured using a resistance meter under conditions of 500V DC / 2s. The insulation resistance of the fluororubber sealing ring was 4.25*10. 9 Ω, below 5000 Mohm (5*10 9 (Ω), the insulation resistance after 50% compression is 2.54*10 9 Ω, below 3000 Mohm (3*10 9 (Ω), which cannot meet CATL's insulation requirements for fluororubber seals.

[0085] Comparing Example 1 with Control Groups 1-2, it can be seen that when the amount of reinforcing composition added to the fluororubber composition is 25 phr, in order to meet CATL's insulation standards, the amount of Cabot N990 carbon black added should be ≤3 phr. Carbon black can enhance hardness, tear resistance, and abrasion resistance, and improve the durability and mechanical strength of rubber. While silica is mainly used to improve the plasticity and tensile strength of rubber materials, its reinforcing effect is not as significant as that of carbon black. Therefore, the optimal addition amount of Cabot N990 carbon black is 4 parts, which improves the mechanical properties, tear resistance, abrasion resistance, and service life of fluororubber seals while meeting CATL's insulation requirements for fluororubber seals.

[0086] Based on the premise that the reinforcing agent consists of 4 parts Cabot N990 carbon black and 21 parts PST-Q02 silica, the influence of different crosslinking agents on the comprehensive performance of fluororubber sealing rings was investigated. Using the crosslinking agent as the sole variable, triallyl isocyanurate TAIC in the fluororubber composition was replaced with trimethylallyl isocyanate, tris(2-acryloyloxyethyl) isocyanurate, diallyl isocyanurate amidation derivative, and mono(acryloyloxyethyl) isocyanurate amidation derivative, respectively, thus forming Examples 2, 3, 4, and 5. The mechanical properties, electrolyte resistance, compression set, and aging resistance of the fluororubber sealing rings in Examples 1-5 were analyzed to determine the influence of different crosslinking agents on the physicochemical properties of the fluororubber sealing rings, thereby screening out the optimal crosslinking agent usage scheme in the formulation.

[0087] Performance testing: Shore hardness, tensile stress-strain properties, compression set, insulation properties, and electrolyte resistance were determined according to GB / T 37996-2019 "Rubber Seals for Power Lithium Batteries". Tear strength was determined according to GB / T 529-2008 "Determination of Tear Strength of Vulcanized Rubber or Thermoplastic Rubber (Pants-shaped, Right-angled, and Crescent-shaped Specimens)".

[0088] Electrolyte resistance performance: color change, mass change rate, and dimensional expansion rate after immersion in electrolyte at 70℃ for 168h. Standard: no change or slight change in electrolyte color after immersion; mass change rate ±15%; dimensional expansion rate ≤20% after immersion in electrolyte.

[0089] Insulation performance: Test the insulation resistance of the fluororubber sealing ring under 500V DC voltage. If the insulation resistance of the fluororubber sealing ring is >5000Mohm, it is qualified; otherwise, it is unqualified. After compression by 50%, the insulation resistance of the fluororubber sealing ring is >3000Mohm, which is qualified; otherwise, it is unqualified.

[0090] The difference between Example 2 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of the crosslinking agent - triallyl isocyanurate is replaced with 4 parts of the crosslinking agent - trimethallyl isocyanate (CAS: 6291-95-8).

[0091] The difference between Example 3 and Example 1 is that in the formulation of the fluororubber composition for sealing lithium batteries, 4 parts of the crosslinking agent - triallyl isocyanurate - are replaced with tris(2-acryloyloxyethyl) isocyanurate (CAS:40220-08-4).

[0092] The difference between Example 4 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of the crosslinking agent - triallyl isocyanurate - are replaced with diallyl isocyanurate amidation derivative.

[0093] The preparation method of diallyl isocyanurate amidation derivative is as follows: 0.1 mol of diallyl isocyanurate and 0.1 mol of 2-(trifluoromethyl)acrylic acid are dissolved in 100 mL of organic solvent - dimethyl sulfoxide. After mixing evenly, 0.5 g of activator - dicyclohexylcarbodiimide DCC is added. The reaction is carried out in a water bath at 50 °C for 24 h. After the reaction is completed, the acid value in the solution is detected. When the acid value is ≤0.01 mg KOH / g, it is considered that the secondary amine group of diallyl isocyanurate has completely reacted with the carboxyl group of 2-(trifluoromethyl)acrylic acid. Then, 0.8 g of polymerization inhibitor benzoquinone is added and mixed evenly. The mixture is then removed by vacuum distillation using organic solvent - dimethyl sulfoxide to obtain diallyl isocyanurate amidation derivative.

[0094] The structural formula of the obtained diallyl isocyanurate amidation derivative is as follows:

[0095] .

[0096] The difference between Example 5 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of the crosslinking agent - triallyl isocyanurate is replaced with 4 parts of the crosslinking agent - isocyanuric acid mono(acryloyloxyethyl) ester amidation derivative.

[0097] The preparation method of the isocyanuric acid mono(acryloyloxyethyl) ester amidation derivative is as follows: 0.1 mol of diallyl isocyanuric acid and 0.2 mol of 2-(trifluoromethyl)acrylic acid are dissolved in 100 mL of dimethyl sulfoxide. After mixing evenly, 0.5 g of activator - dicyclohexylcarbodiimide DCC is added. The reaction is carried out in a water bath at 50 °C for 24 h. If the acid value in the solution is lower than 0.01 mg KOH / g, it is considered that the secondary amine group of isocyanuric acid mono(acryloyloxyethyl) ester has completely reacted with the carboxyl group in 2-(trifluoromethyl)acrylic acid. After adding 0.8 g of polymerization inhibitor benzoquinone and mixing evenly, the dimethyl sulfoxide is removed by vacuum distillation to obtain the isocyanuric acid mono(acryloyloxyethyl) esterification derivative.

[0098] The structural formula of the obtained isocyanuric acid mono(acryloyloxyethyl) ester amidation derivative is as follows:

[0099] .

[0100] Table 1: Physicochemical properties of fluororubber sealing rings in Examples 1-5

[0101]

[0102] As can be seen from Examples 1-5 and Table 1, the mechanical properties, compression set, aging resistance, and electrolyte corrosion resistance of the fluororubber sealing rings prepared in Examples 1-5 all meet the requirements of GB / T 37996-2019. Although the physicochemical properties of the fluororubber sealing rings prepared using different crosslinking agents meet the standards, there are still differences. Using Example 1 as the control standard, the tensile strength of the fluororubber sealing ring prepared in Example 2 using trimethylallyl isocyanate as the crosslinking agent decreased, but its tensile strength, compression set, tear strength, aging resistance, and electrolyte corrosion resistance were relatively better. Using Example 1 as the control standard, the tensile strength, aging resistance, and electrolyte corrosion resistance of the fluororubber sealing ring prepared in Example 3 using tris(2-acryloyloxyethyl) isocyanurate as the crosslinking agent decreased, but its tensile strength, tear strength, and compression set were significantly improved. Using Example 1 as a control standard, the fluororubber sealing rings prepared in Example 4 using a diallyl isocyanurate amidation derivative as a crosslinking agent and Example 5 using a mono(acryloyloxyethyl) isocyanurate amidation derivative as a crosslinking agent showed a decrease in tensile strength and tensile strength, but significant improvements in tear strength, compression set, aging resistance, and electrolyte corrosion resistance, with Example 5 showing the most significant improvement. In summary, the preferred crosslinking agent is a composite crosslinking agent formed by combining at least one of diallyl isocyanurate amidation derivative, or mono(acryloyloxyethyl) isocyanurate amidation derivative, with at least one of these derivatives in combination with at least one of triallyl isocyanurate, trimethylallyl isocyanate, or tris(2-acryloyloxyethyl) isocyanurate.

[0103] Based on 4 parts Cabot N990 carbon black, 21 parts PST-Q02 silica, and 4 parts triallyl isocyanurate, this study investigates the effects of different corrosion-resistant additives and acid absorbers in the formulation of fluororubber compositions on the comprehensive performance of fluororubber sealing rings.

[0104] The difference between Example 6 and Example 1 is that in the formulation of the fluororubber composition for sealing lithium batteries, 4 parts of Cabot N990 carbon black and 21 parts of PST-Q02 silica are replaced with 4 parts of Cabot N990 carbon black, 16 parts of PST-Q02 silica, and 5 parts of 3000-mesh ultrafine barium sulfate. Barium sulfate, 3000 mesh, Hebei Guanchuan New Material Technology Co., Ltd.

[0105] The difference between Example 7 and Example 1 is that in the formulation of the fluororubber composition for lithium battery sealing, 0.3 parts of fluorinated graphene and 3.7 parts of sheet-like nano-molybdenum disulfide are replaced with 3 parts of sheet-like nano-molybdenum disulfide and 1 part of nano-hexagonal boron nitride nanosheets. (Source: Yumu (Ningbo) New Materials Co., Ltd., Product No. BN-100N, Average Particle Size 100nm, Specific Surface Area Density 19m³ / s). 2 / g, bulk density 0.3g / cm³ 3 Density 2.25 g / cm³ 3 .

[0106] The difference between Example 8 and Example 1 is that in the formulation of the fluororubber composition for sealing lithium batteries, 0.3 parts of fluorinated graphene and 3.7 parts of sheet-like nano-molybdenum disulfide are replaced with 3 parts of sheet-like nano-molybdenum disulfide, 0.7 parts of nano-hexagonal boron nitride, and 0.3 parts of fluorinated graphene.

[0107] The difference between Example 9 and Example 1 is that in the formulation of the fluororubber composition for lithium battery sealing, 0.3 parts of fluorinated graphene and 3.7 parts of sheet-like nano-molybdenum disulfide were replaced with 3 parts of sheet-like nano-molybdenum disulfide and 1 part of titanium aluminum carbide (Ti3AlC2)MXene multilayer nanosheets. The titanium aluminum carbide (Ti3AlC2)MXene multilayer nanosheets were obtained by high-speed ball milling of 400-mesh titanium aluminum carbide (Ti3AlC2, product number Brofos-TiALC-3, Bohuas Nanotechnology (Ningbo) Co., Ltd.) using a planetary ball mill at a speed of 400 rpm / 1 h, followed by ball milling at 80 rpm / 30 min to obtain D. 50 =100nm titanium aluminum carbide MXene multilayer nanosheets.

[0108] The difference between Comparative Example 1 and Example 1 is that no corrosion-resistant additives are added to the fluororubber composition, and the corrosion-resistant additives are replaced with an equal amount of silica PST-Q02. The fluororubber composition is made from the following raw materials in parts by weight: 100 parts of fluororubber raw rubber, 4 parts of crosslinking agent - triallyl isocyanurate, 1.5 parts of Luperox® 101XL45, 4 parts of Cabot N990 carbon black, 22.75 parts of silica PST-Q02, 2 parts of magnesium oxide, 4 parts of calcium hydroxide, 4 parts of lead oxide, 5 parts of zinc oxide, 0.3 parts of vinyltrimethoxysilane, 0.7 parts of 3,3,3-trifluoropropylmethyldimethoxysilane, and 0.5 parts of 3853 fine pure fluorine wax.

[0109] Table 2: Physicochemical properties of the fluororubber sealing rings in Examples 6-9 and Comparative Example 1

[0110]

[0111] Based on Examples 1 and 6 and Tables 1 and 3, it can be seen that the physicochemical properties of the fluororubber sealing rings after replacing 5 parts of silica with an equal amount of ultrafine barium sulfate decreased, but all still met the requirements of GB / T 37996-2019. Therefore, barium sulfate can be used as a filler to replace silica.

[0112] Based on Examples 1, 7-9, and Comparative Example 1, and referring to Tables 1 and 3, it can be seen that the physicochemical properties of the fluororubber sealing ring prepared by using sheet-like molybdenum disulfide nanoparticles combined with at least one of fluorinated graphene, nano-hexagonal boron nitride, and MXene nanosheets as a corrosion-resistant additive meet the requirements of GB / T 37996-2019. Fluorinated graphene overcomes the high conductivity of traditional graphene, ensuring the insulation properties of fluororubber while improving the mechanical properties, tear strength, barrier properties, wear resistance, flame retardancy, and electrolyte corrosion resistance of the fluororubber sealing ring.

[0113] To investigate the effect of crosslinking agent addition on the overall performance of fluororubber sealing rings, comparative examples 2-3 were set up with crosslinking agent addition as the sole variable.

[0114] The difference between Comparative Example 2 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of crosslinking agent - triallyl isocyanurate were replaced with 3 parts of crosslinking agent - triallyl isocyanurate.

[0115] The difference between Comparative Example 3 and Example 1 is that in the formulation of the fluororubber composition used for sealing lithium batteries, 4 parts of crosslinking agent - triallyl isocyanurate were replaced with 3 parts of crosslinking agent - triallyl isocyanurate.

[0116] Table 3: Physicochemical properties of fluororubber sealing rings in Example 1 and Comparative Examples 2-3

[0117]

[0118] Based on Example 1, Comparative Examples 2-3 and Table 3, it can be seen that the amount of crosslinking agent added should be controlled at 4 phr. Too much or too little will have an adverse effect on the physicochemical properties of the fluororubber sealing ring. Therefore, the amount of crosslinking agent added is 4 phr, which can ensure that the physicochemical properties of the fluororubber sealing ring meet the requirements of GB / T 37996-2019.

[0119] To investigate the effect of dispersants on the overall performance of fluororubber seals, comparative examples 4-6 were set up with the amount of dispersant added as the only variable.

[0120] The difference between Comparative Example 4 and Example 1 is that no dispersant is added to the fluororubber composition formulation. The fluororubber composition is made from the following raw materials in parts by weight: 100 parts of fluororubber raw rubber, 4 parts of crosslinking agent - triallyl isocyanurate, 1.5 parts of Luperox® 101XL45, 4 parts of Cabot N990 carbon black, 21 parts of white carbon black PST-Q02, 2 parts of magnesium oxide, 3 parts of calcium hydroxide, 4.5 parts of lead oxide, 5 parts of zinc oxide, 0.3 parts of fluorinated graphene, 3.7 parts of flake nano molybdenum disulfide, and 0.5 parts of 3853 fine pure fluorinated wax.

[0121] The difference between Comparative Example 5 and Example 1 is that the fluororubber composition is made from the following raw materials in parts by weight: 100 parts of fluororubber raw rubber, 4 parts of crosslinking agent - triallyl isocyanurate, 1.5 parts of Luperox® 101XL45, 4 parts of Cabot N990 carbon black, 21 parts of white carbon black PST-Q02, 2 parts of magnesium oxide, 3 parts of calcium hydroxide, 4.5 parts of lead oxide, 5 parts of zinc oxide, 0.3 parts of fluorinated graphene, 3.7 parts of flake nano molybdenum disulfide, 0.5 parts of 3853 fine pure fluorine wax, and 1 part of vinyltrimethoxysilane.

[0122] The difference between Comparative Example 6 and Example 2 is that the fluororubber composition comprises the following parts by weight of raw materials: 100 parts of fluororubber raw rubber, 4 parts of crosslinking agent - triallyl isocyanurate, 1.5 parts of Luperox® 101XL45, 4 parts of Cabot N990 carbon black, 21 parts of white carbon black PST-Q02, 2 parts of magnesium oxide, 3 parts of calcium hydroxide, 4.5 parts of lead oxide, 5 parts of zinc oxide, 0.3 parts of fluorinated graphene, 3.7 parts of flake nano molybdenum disulfide, 0.5 parts of 3853 fine pure fluorine wax, and 1 part of 3,3,3-trifluoropropylmethyldimethoxysilane.

[0123] Table 4: Physicochemical properties of the fluororubber sealing rings in Example 1 and Comparative Examples 4-6

[0124]

[0125] Based on Examples 1, Comparative Examples 4-6, and Table 4, it is evident that without modification of the reinforcing composition, acid scavenger, and corrosion-resistant additives using dispersants, the uniformity of dispersion of these components in the fluororubber raw material is poor, thus affecting the electrolyte corrosion resistance, mechanical properties, and compression set properties of the fluororubber sealing ring. Comparing Example 1 with Comparative Examples 5-6, it is clear that the fluororubber sealing ring in Comparative Example 6, which underwent surface modification treatment with fluorosilane alone, exhibits better electrolyte corrosion resistance, mechanical properties, and compression set properties than the fluororubber sealing ring in Comparative Example 5, which did not undergo surface modification with fluorosilane. Therefore, it is concluded that modification of the reinforcing composition, acid scavenger, and corrosion-resistant additives with fluorosilane is beneficial for improving the electrolyte corrosion resistance, mechanical properties, and compression set properties of the fluororubber sealing ring. Although the physicochemical properties of the fluororubber sealing rings in Comparative Examples 5-6 were improved, their physicochemical properties were still inferior to those of the fluororubber sealing ring in Example 1. Therefore, the fluororubber sealing rings prepared using a dispersant composition formed by compounding fluorosilanes and vinylsilanes exhibit superior overall performance, with better tear strength, compression set, resistance to electrolyte corrosion, mechanical properties, and aging resistance.

[0126] Based on Examples 1, Comparative Examples 4-6, and Table 4, it can be seen that using vinyl silane as a dispersant to modify the reinforcing composition, acid scavenger, and corrosion resistant additives results in better physicochemical properties of the fluororubber sealing rings prepared without dispersant modification. However, the mechanical properties of the fluororubber sealing rings prepared in Comparative Example 5 are lower than those prepared in Comparative Example 6. The vinyl groups on the surface of the mixed filler undergo chemical grafting with the vinyl groups in the fluororubber raw rubber under the influence of a thermal field and peroxides, increasing the crosslinking density and thus increasing the hardness of the fluororubber sealing rings. However, the dispersion performance of vinyl silicone oil on the mixed filler is relatively worse than that of fluorosilicone oil. Although it improves the hardness of the fluororubber sealing rings, its mechanical properties and resistance to electrolyte corrosion remain inferior. Therefore, fluorosilane modification allows the reinforcing composition, acid scavenger, and corrosion resistant additives to be more uniformly dispersed within the fluororubber raw rubber, which is more conducive to improving the physicochemical properties of the fluororubber sealing rings. Therefore, using a mixture of fluorosilane and vinylsilane to form a dispersant can improve the uniformity of dispersion of reinforcing composition, acid absorbent, and corrosion resistant additives in fluororubber raw rubber, which is beneficial to improving the overall performance of fluororubber sealing rings. Preferably, the mass ratio of vinyl silicone oil to fluorosilane is controlled at 3 / 7.

[0127] The difference between Example 10 and Example 1 is that in the formulation of the fluororubber composition for sealing lithium batteries, 5 parts of zinc oxide are replaced with 5 parts of 2000 mesh rubber vulcanizing activator - Jieculian II (Guangxi Liankehua New Materials Co., Ltd.).

[0128] The difference between Example 11 and Example 1 is that in the formulation of the fluororubber composition for sealing lithium batteries, 2 parts magnesium oxide, 4 parts calcium hydroxide, and 4 parts lead oxide are replaced with 4 parts magnesium oxide and 6 parts calcium hydroxide.

[0129] The difference between Example 12 and Example 5 is that: a fluororubber composition for sealing lithium batteries is made from the following raw materials in parts by weight: 100 parts of fluororubber raw rubber - Chemours GF600S, 4 parts of crosslinking agent - isocyanuric acid mono(acryloyloxyethyl) ester amidation derivative, 1.5 parts of Luperox® 101XL45, 4 parts of Cabot N990 carbon black, 21 parts of silica PST-Q02, 4 parts of nano magnesium oxide SS-MG30, 6 parts of calcium hydroxide HP-XL, 5 parts of rubber vulcanizing activator - Jieculian II, 0.3 parts of fluorinated graphene, 1.7 parts of nano hexagonal boron nitride nanosheets, 2 parts of sheet-like nano molybdenum disulfide, 0.3 parts of vinyltrimethoxysilane KH-171, 0.7 parts of 3,3,3-trifluoropropylmethyldimethoxysilane, and 0.5 parts of 3853 fine pure fluorinated wax.

[0130] Table 5: Physicochemical properties of fluororubber sealing rings in Examples 1 and 10-12

[0131]

[0132] Combining Examples 1 and 10 with Table 5, it can be seen that the rubber vulcanizing activator, Jieculian Type II, can replace nano zinc oxide, giving fluororubber sealing rings better environmental performance.

[0133] Combining Examples 1 and 11 with Table 5, it can be seen that the addition of lead oxide is beneficial to improving the electrolyte corrosion resistance of fluororubber sealing rings. However, from an environmental perspective, lead oxide is detrimental to the environmentally friendly production of fluororubber sealing rings. From the perspective of lithium battery development, fluororubber sealing rings are used for sealing lithium battery electrolytes. In this application scenario, the wear rate of fluororubber sealing rings is low, and the fluororubber sealing rings can be recycled after the lithium battery is scrapped, limiting the ecological diffusion and toxicity of lead oxide. Lead oxide can be added to fluororubber sealing rings as an acid absorber. To overcome the potential ecological diffusion and toxicity problems of lead oxide, the inventors optimized the fluororubber formulation by using nano-hexagonal boron nitride to replace lead oxide. Although the production cost increased, it improved the barrier properties and electrolyte corrosion resistance of fluororubber sealing rings and eliminated the potential ecological diffusion and toxicity problems of lead oxide, thus facilitating the environmentally friendly production of fluororubber sealing rings.

[0134] In summary, the fluororubber sealing ring prepared in this invention has good resistance to electrolyte corrosion, as well as good wear resistance, weather resistance, and tensile strength, which improves the sealing quality and safety stability of lithium battery electrolyte and promotes the high-quality and safe development of lithium batteries.

[0135] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A fluororubber composition for use in sealing lithium batteries, characterized in that: It is made from the following raw materials in parts by weight: 100 parts of fluororubber raw rubber, 3.8-4.2 parts of crosslinking agent, 1.3-1.6 parts of peroxide, 28-36 parts of reinforcing composition, 6-12 parts of acid absorber, 3-5 parts of corrosion resistant additive, 0.5-2 parts of dispersant, and 0.5-1 parts of release agent.

2. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The fluororubber raw material is any one of Chemours GF200S, Chemours GF600S, Daikin G932, Solvay P459, Solvay P959, Solvay PL 458, Solvay PL958, and 3M-FP03820.

3. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The crosslinking agent includes at least one of triallyl isocyanurate, trimethylallyl isocyanate, tri(2-acryloyloxyethyl) isocyanurate, diallyl isocyanurate amidation derivative, and isocyanurate mono(acryloyloxyethyl) isocyanurate amidation derivative.

4. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The reinforcing composition comprises a reinforcing agent and a filler. The reinforcing agent is any one of silica combined with carbon black, calcium oxide, and zinc oxide. The filler is any one of barium sulfate, titanium dioxide, and calcium fluoride.

5. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The corrosion-resistant additive is any one of fluorinated graphite powder, fluorinated graphene, MXene nanosheets, nano-hexagonal boron nitride, and sheet-like nano-molybdenum disulfide.

6. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The dispersant is composed of vinyl silicone oil and fluorosilane; the vinyl silicone oil is vinyltrimethoxysilane and / or vinyltri(2-methoxyethoxy)silane; the fluorosilane is any one of tridecafluorooctyltrimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, and 3,3,3-trifluoropropylmethyldimethoxysilane.

7. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The acid absorbent is composed of magnesium oxide, calcium hydroxide and lead oxide in a mass ratio of (2-3):(2-5):(3-5).

8. The fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The peroxide is at least one of dicumyl peroxide, benzoyl peroxide, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane.

9. A fluororubber composition for sealing lithium batteries according to claim 1, characterized in that: The release agent is any one of 3853 fine pure fluorine wax, PTFE / PE micro powder wax ST-563F, polytetrafluoroethylene modified wax 9610F, and zinc stearate.

10. A method for preparing a fluororubber composition for sealing lithium batteries as described in claims 1-9, characterized in that: Includes the following steps: Step 1: The reinforcing composition, acid absorber, and corrosion resistant additive are surface-treated with a dispersant to obtain a mixed filler; Step 2: Mix the mixed filler from Step 1 with the crosslinking agent, peroxide, and release agent until homogeneous to obtain the premix. Step 3: Add the fluororubber raw rubber to a two-roll mill and mix at 40-60℃ for 1-2 minutes. Then add the premix from Step 2, make triangular bags 2-6 times, and pass through a thin tube 4-8 times. Let it stand for 1-24 hours to obtain the compound rubber. Step 4: Compression molding to prepare fluororubber sealing rings: The compounded rubber is injected into the molding die, followed by two-stage vulcanization treatment by moving the die. The first stage vulcanization temperature is 170-185℃, the pressure is 8-16MPa, and the time is 8-12 minutes; the second stage vulcanization temperature is 210-230℃ and the time is 2-6 hours. Finally, hot pressing is performed at 200-220℃ and 1-3 MPa pressure for 40-80 minutes. After natural cooling to room temperature, the rings are demolded and the burrs are trimmed to obtain fluororubber sealing rings for lithium battery sealing.

Citation Information

Cited By

  • Polyvinyl chloride insulated cable material and preparation method thereof

    CN121495271A